2019
DOI: 10.3855/jidc.11240
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection incidence and risk factors in thoracic surgical procedures: A 12-year prospective cohort study

Abstract: Introduction: Surgical site infections (SSI) continue to be a major problem for thoracic surgery patients. We aimed to determine incidence rate (IR) and risk factors for SSI in patients with thoracic surgical procedures. Methodology: During 12 years of hospital surveillance of patients with thoracic surgical procedures, we prospectively identified SSI. Patients with SSI were compared with patients without SSI. Results: We operated 3,370 patients and 205 (6.1%) developed SSI postoperatively. We dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The overall SSI rate was 1.5%, which reflects current literature rates mentioned above (6)(7)(8)(9)(10)(11). There is no consensus on criteria for the diagnosis of SSI (1,4,18).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The overall SSI rate was 1.5%, which reflects current literature rates mentioned above (6)(7)(8)(9)(10)(11). There is no consensus on criteria for the diagnosis of SSI (1,4,18).…”
Section: Discussionsupporting
confidence: 52%
“…Only 36 of the 512 anatomical resections were performed with VATS. Cvijanović et al reported a SSI rate of 6.1% in thoracic surgery in 3,370 patients over a 12-year period (VATS: 2.14%, Open 7.1%), but the result was not significant in a multivariate analysis aiming to identify SSI risk factor and only 30 of the 1,319 anatomical resections were performed by VATS (10). In all these studies, the compared groups were rather heterogeneous, and although the study of Cvijanović et al is one of the largest studies investigating this matter in thoracic surgery so far, the long study period includes a lot of changes in patient treatment (used disinfectant, preoperative antibiotics, surgical technique, etc.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 There is support in the literature of lower incidence of surgical site infections with minimally invasive approach compared to thoracotomy. Recently, Cvijanović et al published a 12-year retrospective study comparing risk factors and incidence of surgical site infections (SSI) in thoracic surgical procedures including wedge resection, lobectomy, and pnuemontoecmy 24 with reported cumulative SSI rates of 2.2% in the VAT surgical group compared to 3.5% after open thoracotomy. However, no segmentectomy group was reported in the study.…”
Section: Discussionmentioning
confidence: 99%